Integrasi Nilai-nilai Islam dalam Pemanfaatan Teknologi Digital oleh Generasi Z di Era Moderen: Integration of Islamic Values in the Use of Digital Technology by Generation Z in the Modern Era - Devita Putri Maharani; Adinda Sekar Suryaningrum; Diva Amalia Nuraini; Oktaviola Wahyu Nur Anggraini; Devi Ayu Yuliani; Aprilia Prahesti; Ahmad Nurrohim (DIRASAH: Jurnal Kajian Islam, 2025)
Generation Z grew up amidst the rapid development of digital technology, which influenced the way they accessed and spread Islamic values. Technology, especially social media and digital applications, provides opportunities for this generation to explore religious teachings, as well as convey religious messages to a wider audience in innovative and relevant ways. However, challenges faced include dependence on the digital world which can divert focus from religious practices and the risk of being exposed to information that is not always in accordance with Islamic values. However, with critical skills and community support, Generation Z can use technology to integrate Islamic values ​​in everyday life and play an active role in spreading religious teachings in modern society. Digital technology, if used wisely, can be an effective means of strengthening their religious identity.